MENUMBUHKAN KEPEDULIAN TERHADAP PENANGGULANGAN PEREKONOMIAN BAGI ANAK YATIM DAN DHUAFA - Angelica Richard Eka Putri; Isfandayani Isfandayani; Ria Marginingsih (An-Nizam, 2022)
Poverty is an important problem related to population in many countries, including Indonesia. In 2020, Indonesia was hit by the Covid-19 pandemic which hit the economic sector and people's lives, in addition to health itself. The Central Statistics Agency (BPS) stated that the number of poor people in Indonesia increased by more than 2.7 million people due to the Covid-19 pandemic. Poverty is a human problem. From this dimension, the existence of poverty carries the consequence of a moral responsibility for everyone to pay attention to the lives of people living in poverty. Poverty is also a violation of human rights. In dealing with the economy, as a person who has high tolerance and solidarity, he will optimize his actions to overcome the economy by collecting funds from several people who have the same mission in tackling the economy, especially in the field of education for orphans and poor people. Because education is the foundation for overcoming poverty in the future. This study uses a descriptive approach by making observations and providing optimization efforts to overcome the economy by using the Education Assistance Fund program funds in the Pengasinan area, Rawalumbu, Bekasi.